2017
DOI: 10.7567/jjap.56.10pc05
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependences of the electromechanical and electrocaloric properties of Ba(Zr,Ti)O3and (Ba,Sr)TiO3ceramics

Abstract: The electrocaloric properties of Ba(Zr,Ti)O3 and (Ba,Sr)TiO3 ceramics (BZT and BST, respectively) were investigated by the indirect estimation and direct measurement of temperature–electric field (T–E) hysteresis loops. The measured T–E loops had shapes similar to those of the strain–electric field (s–E) loops. The measured temperature changes (ΔTs) at around 30 °C of the BZT ceramics sintered at 1450 °C and BST ceramics sintered at 1600 °C upon the release of the electric field from 30 kV/cm to 0 were 0.34 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The measurements were performed as described in previous reports. [23][24][25][26][27] When measuring the ferroelectric properties and electric field-induced strain of the piezoelectric ceramics themselves, a sample cut out from a diaphragm into a 2 mm square was used.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurements were performed as described in previous reports. [23][24][25][26][27] When measuring the ferroelectric properties and electric field-induced strain of the piezoelectric ceramics themselves, a sample cut out from a diaphragm into a 2 mm square was used.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Measurements of the electrocaloric effects were performed as in previous reports. [23][24][25][26][27] To produce electrocaloric effects, an alternating electric field was applied to an electrode from an external power source, and temperature changes due to electrocaloric effect and electric field-induced strain were measured. To measure the elastocaloric effects, the piezoelectric diaphragm was sandwiched between plastic supports so that the section of the diaphragm circle was located 13 mm from the center of the diaphragm.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11–14 ] Among the lead‐free systems, the zirconium (Zr)‐ and tin (Sn)‐doped BaTiO 3 system has emerged as a potential candidate for EC applications due to its high dielectric constant and its proximity to the ferroelectric–paraelectric phase transition point. [ 14,15 ] This system has been extensively studied, and Kacem et al [ 16 ] observed a near‐room‐temperature transition in BaTi 0.91 Sn 0.08 Zr 0.01 O 3 ceramics, which improved the dielectric, pyroelectric, and EC properties of the samples. Although block ceramics have been recognized for their high refrigeration volume and large refrigeration capacity, their limited breakdown field strength hinders the achievement of a large ECE.…”
Section: Introductionmentioning
confidence: 99%
“…From an environmental viewpoint, concerns of toxicity in Pb have caused a strong demand to develop Pb-free piezoelectric materials. There has been an intense effort to investigate Pb-free piezoelectric materials such as Ba-based, [10][11][12][13][14] Bi-based 10,[15][16][17][18][19] and Nb-based [20][21][22][23][24][25][26][27] ferroelectrics. Among them, bismuth sodium titanate (Bi 1/2 Na 1/2 )TiO 3 (BNT) and its solid solutions are recognized as promising Pb-free materials due to their superior properties.…”
Section: Introductionmentioning
confidence: 99%